2018
DOI: 10.1177/0363546518780934
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Surgical Treatment for Anterior Shoulder Instability: A Systematic Review

Abstract: When treating an athlete, many factors must be taken into account to weigh treatment options. Two important factors to consider with the patient-athlete are the rate of return to the previous activity level and the timeline for this to occur. This study provides a guide for physicians and a time frame for athletes with respect to the mean percentage and time for return to sport after different surgical procedures for anterior shoulder instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
102
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 38 publications
5
102
4
2
Order By: Relevance
“…Whereas some larger studies have reported losses in ER after remplissage, others have reported no statistically significant difference 20, 28, 29, 30, 31, 32, 33. Remplissage continues to have comparable return-to-sport rates to the open Latarjet procedure; however, some concern exists for throwing athletes 34, 35, 36. In their 2016 case series, Garcia et al 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some larger studies have reported losses in ER after remplissage, others have reported no statistically significant difference 20, 28, 29, 30, 31, 32, 33. Remplissage continues to have comparable return-to-sport rates to the open Latarjet procedure; however, some concern exists for throwing athletes 34, 35, 36. In their 2016 case series, Garcia et al 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the success of shoulder instability surgery is largely defined by the lack of recurrence, the time to return to sport has emerged as an important and clinically significant metric indicative of success following shoulder stabilization. 1 A recent systematic review of 16 articles 1 reported a return to sport rate of 97.5% and 83.6% after arthroscopic Bankart and open Latarjet procedures, respectively. Furthermore, the time to return to sport was 5.07 months for Latarjet compared with 5.9 months after arthroscopic Bankart.…”
Section: Discussionmentioning
confidence: 99%
“…Although this hypothesis has not been adequately studied, comparative studies have suggested that patients undergoing Latarjet procedures return to sport more quickly than patients undergoing arthroscopic Bankart repair. 1,11 Accordingly, the purpose of the current study was to (1) define the degree of variability across rehabilitation protocols published online for the Latarjet procedure and (2) compare Latarjet rehabilitation programs with published Bankart repair protocols. We hypothesized that the consistency of the programs would vary widely and there would be substantial temporal differences in milestones between Latarjet and Bankart protocols.…”
mentioning
confidence: 99%
“…[16][17][18] Arthroscopic techniques offer the potential advantage of decreased morbidity, with several studies demonstrating faster return to preoperative function and return to sport. [19][20][21][22] However, many studies have generated concern about arthroscopic stabilization techniques in certain patient populations due to reported higher rates of recurrent instability and decreased time to recurrence when compared to open techniques. [23][24][25][26][27][28] More specifically, increased failure of arthroscopic techniques has been demonstrated in the presence of large glenohumeral bony defects.…”
mentioning
confidence: 99%